2023
DOI: 10.1128/spectrum.00634-23
|View full text |Cite
|
Sign up to set email alerts
|

Tigecycline Resistance-Associated Mutations in the MepA Efflux Pump in Staphylococcus aureus

Abstract: Previous analysis has shown that overexpression of MepA is an exact mechanism involved in tigecycline resistance apart from the rpsJ mutation and is usually dependent on the mutant mepR . However, no research has evaluated the effects of diverse mutations discovered in TRSA in MepA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A single B/GBS Int 9.2 prophage was found to carry a gene encoding a multidrug and toxic compound extrusion (MATE)-like protein, similar to MepA from Staphylococcus aureus [41]. It has been reported that expression of MATE proteins in bacteria confers resistance to toxic dyes and multiple antibiotics [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…A single B/GBS Int 9.2 prophage was found to carry a gene encoding a multidrug and toxic compound extrusion (MATE)-like protein, similar to MepA from Staphylococcus aureus [41]. It has been reported that expression of MATE proteins in bacteria confers resistance to toxic dyes and multiple antibiotics [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…This study's results confirm a similar synergistic effect in the Gram-positive bacterium S. aureus. The S. aureus ATCC 33593 contains four genes (mepA, norA, norB, and sdrM) encoding antibiotic efflux pumps; MepA is known to efflux aminoglycosides and fluoroquinolone antibiotics [3,43]. Tobramycin is an aminoglycoside, and it has been suggested that tobramycin is effluxed by MepA.…”
Section: Corydalis Tuber Extract and Berberine Are Efflux Pump Inhibi...mentioning
confidence: 99%